PENINGKATAN KEMAMPUAN GURU SEKOLAH DASAR DALAM PEMBUATAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA - Rizkayeni Marta; Vera Irma Delianti; Yeka Hendriyani (Jurnal Teknologi Informasi dan Pendidikan, 2019)
The purpose of this article is to find out the improvement of ability of elemenatry school teachers in Gugus 01 Baringin Anam Kecamatan Baso kabupaten Agam to create multimedia based on learning media by using Macromedia Director aplication. The improvement of ability is measured by using pre-test and post-test. The pre-test result that given to 20 teachers gained an average of 46.6 and the post-test result gained an average of 71. Based on the data, the increased percentage of elementary school teacher's ability was 52.36%. Thus, it can be concluded that there is an increase in the ability of elementary school teachers in Gugus 01 Baringin Anam Kecamatan Baso Kabupaten Agam.